Diversity and dynamics of Archaea in an activated sludge wastewater treatment plant - Fredriksson, Nils Johan (BioMed Central, 2012)
BACKGROUND: The activated sludge process is one of the most widely used methods for treatment of wastewater and the microbial community composition in the sludge is important for the process operation. While the bacterial communities have been characterized in various activated sludge systems little is known about archaeal communities in activated sludge. The diversity and dynamics of the Archaea community in a full-scale activated sludge wastewater treatment plant were investigated by fluorescence in situ hybridization, terminal restriction fragment length polymorphism analysis and cloning and sequencing of 16S rRNA genes. RESULTS: The Archaea community was dominated by Methanosaeta-like species. During a 15 month period major changes in the community composition were only observed twice despite seasonal variations in environmental and operating conditions. Water temperature appeared to be the process parameter that affected the community composition the most. Several terminal restriction fragments also showed strong correlations with sludge properties and effluent water properties. The Archaea were estimated to make up 1.6% of total cell numbers in the activated sludge and were present both as single cells and colonies of varying sizes. CONCLUSIONS: The results presented here show that Archaea can constitute a constant and integral part of the activated sludge and that it can therefore be useful to include Archaea in future studies of microbial communities in activated sludge.